Formalising and animating multiple instances in BPMN collaborations. Issue 103 (January 2022) - Corradini, Flavio; Muzi, Chiara; Re, Barbara; Rossi, Lorenzo; Tiezzi, Francesco
Abstract: The increasing adoption of modelling methods contributes to a better understanding of the flow of processes, from the internal behaviour of a single organisation to a wider perspective where several organisations exchange messages. In this regard, BPMN collaborations provide a suitable modelling abstraction. Even if this is a widely accepted notation, only a limited effort has been expended in formalising its semantics, especially for what it concerns the interplay among control features, data handling and exchange of messages in scenarios requiring multiple instances of interacting participants. In this paper, we face the problem of providing a formal semantics for BPMN collaborations including elements dealing with multiple instances, i.e., multi-instance pools and sequential/parallel multi-instance tasks. For an accurate account of these features, it is necessary to consider the data perspective of collaboration models, thus supporting data objects, data collections and data stores, and different execution modalities of tasks concerning atomicity and concurrency. Beyond defining a novel formalisation, we also provide a BPMN collaboration animator tool, named MIDA, faithfully implementing the formal semantics. MIDA  can also support designers in debugging multi-instance collaboration models. Highlights: We provide a novel comprehensive approach to formalise multi-instance BPMN collaborations. We clarify the interplay among multiple instances, data and messages. We have developed a modelling and animation tool for BPMN collaborations.